The Feasibility of Project-Based Learning E-Worksheet on The Topic of Ecosystems for Training Problem-Solving Skills in Grade X High School Students - Safitri, Matiin Indi; Purnomo, Tarzan (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
Problem-solving skills are one of the important abilities that students need to have in order to face the challenges of the 21st century. This study aims to produce an E-LKPD based on Project Based Learning (PjBL) on ecosystem to train the problem-solving skills of 10th grade high school students, based on the validity and completeness of the students' cognitive learning outcomes. This study used the 4-D model (Define, Design, Develop, and Disseminate), with a limited trial involving 20 tenth-grade students at SMAN Jogoroto, Jombang. The validity instruments consisted of 19 items covering presentation, content, and language, which were adapted to the PjBL learning model and problem-solving indicators. This assessment was conducted by media experts, subject matter experts, and high school biology teachers using a Likert scale of 1-4 (poor-very good). The completeness of cognitive learning outcomes was assessed through the completion of pre-test and post-test using the N-Gain value calculation based on the school's minimum passing grade (KKM). Data analysis was conducted using quantitative descriptive analysis. The validity based on the presentation aspect was 98.33%, the content aspect was 98.08%, and the language aspect was 100%. Overall, the validity score was 98.80% (highly valid). The cognitive learning outcomes of the students achieved an average score of 88 and an N-Gain of 0.76, categorized as high improvement. Based on these results, the E-LKPD based on PjBL on the ecosystem topic is deemed suitable for implementing problem-solving skills training for 10th-grade high school students, as evaluated by validity and cognitive learning outcomes.